(untitled) (Tạp chí Y học Cộng đồng, 2025)
Introduction: Pelvic fractures are severe injuries associated with a high mortality rate due to shock and hemorrhage, particularly in cases of unstable fractures. Internal fixation surgery plays a critical role in restoring both anatomical structure and functional integrity. Objective: This study aims to evaluate the outcomes of internal fixation in the treatment of pelvic fractures at Bach Mai Hospital and to identify factors influencing surgical results. Methods: A retrospective cross-sectional study was conducted at Bach Mai Hospital, involving 30 patients with pelvic fractures who met the surgical indication criteria and were eligible for inclusion. Data were analyzed using SPSS version 20.0, with statistical significance set at p < 0.05. Results: The study included 30 patients who underwent internal fixation for pelvic fractures at the Department of Orthopedic Trauma and Spine Surgery, Bach Mai Hospital. The mean patient age was 49.1 ± 17.2 years, with a male-to-female ratio of 3:2. The predominant cause of injury was traffic accidents. According to the AO classification, type B fractures accounted for the highest proportion (63.3%), while the most common injury mechanism, according to the Young–Burgess classification, was lateral compression (LC). Complications included internal iliac vein rupture (1 case, 3.3%), pressure ulcers (4 cases, 16.7%), superficial surgical site infection (1 case, 3.3%), and posterior tibial vein thrombosis (1 case, 3.3%). The mean operative time was 76.73 ± 26.15 minutes. Treatment outcomes were assessed using the Iowa Pelvic Score, Majeed Pelvic Score, and IIEF, indicating favorable recovery; the average IIEF score was consistent with the published literature. Conclusion: Internal fixation for pelvic fractures yields good recovery outcomes with a low rate of complications when appropriately indicated and technically well-executed.